Peer to peer file sharing system using IPFS and blockchain - Ahmam, Ammar Arief Ainol; Endut, Nor Adora (College of Computing, Informatics, and Mathematics, 2025)
This paper presents a peer to peer (P2P) file sharing system designed on top of Interplanetary File System (IPFS) and blockchain. Decentralized storage solutions that enable programmatic file accessibility, security and reliability as well as eliminating bottlenecks, scaling problems, and user experience limitations in web based P2P application are explored. It integrates IPFS to store and retrieve the files using content-based addressing and. Pinata is also used for file pinning and keeping the file in the network free availability, and Helia is a JavaScript based interface for web application to communicate with IPFS. To increase security and transparency, decentralized verification is conducted via smart contracts on Ethereum by permanently logging a file hash record. With Meta Mask and Web3 technologies for secure payment, users can handle storage and access payment to services effectively. Despite these advancements, web based P2P programs have considerable challenges. Since they can run on limited processing power, storage, and fragile net stability, the processing is carried out in the client side, and that means slow file transfers and high latency. Moreover, the acceptance of decentralized applications is also hindered by the fact that users must understand the cryptographically based transactions and other complex concepts such as IPFS hashes. In this paper, we attempt to find approaches to improve performance on cryptographic computations using WASM, cache adaptive for faster download, and Ethereum Layer 2 solutions like rollups reducing transaction costs and improving scalability. Aside from that, associating with the File coin to facilitate growth of the distribution storage is considered to support the system growth